PSO based Optimal Placement of Distributed Generation for Loss Minimization and Voltage Profile Improvement under Contingencies - Srivastava A.; Barnwal A.K.; Verma M.K. (My University, 2025)
Power systems are desired to operate within defined limits of voltages and line power flow. But many times, they get severely constrained and breach these limits and therefore the security of power system gets compromised. Such challenging situations generally occur in case of occurrence of some form of contingency in the system. Contingency can be a simple one such as a line outage or a complex one like cascade line outages leading to blackout etc. To suggest some ways to save the system from disastrous consequences of these contingencies is the motivation of the present work. This work is synthesized basically in two parts. First part deals with the study of contingency in detail, such as, in what form it occurs, where in a power system it could be most severe etc. For this part some power flow indices have been calculated via simulations and then these indices are used to determine severity in each case. The second part makes an attempt to propose a way out to mitigate the negative impacts of these contingencies which usually are driving the system beyond its operational limits in terms of bus voltages, line power flows etc. The technique proposed in this part is the use of Distributed Generations optimally in the power system to increase its reliability. All simulations in this paper are carried out in MATLAB environment and test system deployed for this work is IEEE 6 bus system. © 2022 IEEE.